CHARACTERIZING SOIL ORGANIC MATTER IN ARCTIC TUNDRA SOILS BY DIFFERENT ANALYTICAL APPROACHES - Dai X.Y.; Ping C.L.; Michaelson G.J. (My University, 2002)
Soil organic matter (SOM) of five soil horizons from Arctic tundra and one soil horizon from a temperate region was separated into an extractable fraction (EF) and a non-extractable fraction (NEF) by dilute alkali. The modified classical fractionation method was applied to characterize SOM in the EF; and the wet chemical fractionation scheme, cross-polarization magic angle spinning (CP-MAS) 13C NMR, and pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) techniques were used to characterize SOM in the NEF. Each of these methods provides information on the chemical composition of SOM at varying angles. The NEF comprises a large amount of SOM in these arctic tundra soils and has great potential to influence carbon cycling in these ecosystems with climate warming.